Directive Speech Act of Influencers in Endorse on Instagram Social Media - Amalia, Anisa; Rokhman, Fathur; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Influencers in supporting a product (endorse) on Instagram, of course, make various utterances to attract other Instagram users to buy the product being promoted. In promoting or supporting their products, Influencer speech can be in the form of words in photos or videos uploaded on grid profiles or on Instagram stories. The purpose of this study is to find and describe the types of Influencer directive speech acts contained in Endorse on Instagram social media, find, and describe the pragmatic function of directive speech acts contained in Endorse on Instagram social media, and describe the effect of Influencer directive speech acts on Endorse on Instagram. Instagram social media. This study uses two approaches, namely a theoretical approach and a methodological approach. The methodological approach in this study is a qualitative descriptive approach because the research data is not in the form of numbers, but in the form of words or utterances made by Influencers contained in Endorse on Instagram social media. So the research that will be achieved is to describe the types, functions and effects of Influencer directive speech acts in Endorse on Instagram social media. The results of the study show that in Influencers' directive speech acts in Endorse on Instagram social media, there are various types of directive speech acts such as: (1) types of directive speech acts requests with functions of asking, inviting; (2) questioning with the function of giving question; (3) requiring with the function of require directly; (4) prohibition with the function of prohibiting; (5) granting permissions with the function of conferring; (6) advising with the function of giving advice, suggesting. In the Influencer's directive speech acts in Endorse on Instagram social media, two effects were found: (1) positive effects: attracted, relieved, encouraged, and made grateful; (2) negative effects: frightening, jealousy, mistrust.